Effect of high Lewis number on the non-adiabatic premixed flame edges. (2017) - Al-Sarairah, E.
In this paper, we investigate numerically the influence of heat loss and Damköhler number, which is inversely proportional to the square of strain rate, on the edges of premixed flames in a two dimensional counterflow for Lewis numbers greater than unity. The propagation speed of flame edges is plotted against Damköhler numbers for different values of the heat loss parameter showing a multiple flame edge solutions in the form of S shaped curves.